Improving Student Citizenship Education Learning Outcomes through Cooperative Learning Types of Group Investigations in Class X.3 State Senior High School Makassar - Musdalifah Syahrir (JED (Jurnal Etika Demokrasi), 2022)
This research is a class action research (classroom action research) which aims to improve student-learning outcomes in class X.3 State Senior High School Makassar through a cooperative learning type investigation group (Group Investigation). The subjects of this study amounted to 39 people, consisting of 14 males and 25 females. This research was conducted in two cycles. From cycle I to cycle II, the cooperative learning model of group investigation type (Group Investigation) is used by continuously improving the quality of group learning implementation. As for the results of the research conducted over two cycles, it can be concluded that: 1) Group investigation type cooperative learning (Group Investigation) can improve student learning outcomes in Class X.3  State Senior High School Makassar in Civics Learning, 2) Student learning outcomes increase based on the achievement of scores which has exceeded the criteria of success with a very good category. The achievement is that the deficiencies in the first cycle can be overcome so that there is an increase in student activity which is indicated by an increase in student learning outcomes in the high category. The conclusion that can be drawn from the results of this study is that the application of the group investigation type learning model (Group Investigation) can improve student learning outcomes in Civics subjects in class X.3 State Senior High School Makassar.Penelitian ini adalah penelitian tindakan kelas (classroom action research) yang bertujuan untuk meningkatkan hasil belajar siswa kelas X.3 SMAN 10 Makassar melalui pembelajaran kooperatif tipe investigasi kelompok (Group Investigation). Subjek penelitian ini berjumlah 39 orang, terdiri dari 14 orang laki-laki dan 25 orang perempuan. Penelitian ini dilaksanakan dalam dua siklus. Dari siklus I ke siklus II menggunakan model pembelajaran kooperatif tipe investigasi kelompok (Group Investigation) dengan senantiasa meningkatkan kualitas pelaksanaan belajar kelompok. Adapaun hasil penelitian yang dilaksanakan  selama dua siklus dapat disimpulkan bahwa : 1) Pembelajaran kooperatif tipe investigasi kelompok (Group Investigation) dapat meningkatkan hasil belajar siswa Kelas X.3 SMA Negeri 10 Makassar dalam Pembelajaran PKn, 2) Hasil belajar siswa meningkat didasarkan pada pencapaian skor yang telah melampaui kriteria keberhasilan dengan kategori sangat baik. Adapun pencapaiannya yaitu kekurangan yang terdapat pada siklus I sudah dapat diatasi sehingga terjadi peningkatan keaktifan siswa yang ditunjukkan dengan peningkatan hasil belajar siswa yang berada pada kategori tinggi. Kesimpulan yang dapat ditarik dari hasil penelitian ini adalah penerapan model pembelajaran tipe investigasi kelompok (Group Investigation) dapat meningkatkan hasil belajar siswa pada mata pelajaran PKn kelas X.3 SMA Negeri 10 Makassar.